Is the abnormal return following equity issuances anomalous? - Brav, Alon; Geczy, Christopher; Gompers, Paul A. (Journal of Financial Economics, 2000)
We examine whether a distinct equity issuer underperformance anomaly exists. In a sample of initial public offering (IPO) and seasoned equity offering (SEO) firms from 1975 to 1992, we find that underperformance is concentrated primarily in small issuing firms with low book-to-market ratios. SEO firms, that underperform these standard benchmarks have time series returns that covary with factor returns constructed from nonissuing firms. We conclude that the stock returns following equity issues reflect a more pervasive return pattern in the broader set of publicly traded companies.